Amenorrea Primer - Nurul Islamy; Odi Wijaya; nur sazaro tudhur; Anggita Dwi Paramitha (CV. Jasa Sukses Abadi, 2021)
Amenorrhea is defined as the absence of menarche in females of reproductive age. Primary amenorrhea is defined as the failure to initiate menses by age 14 in the absence of secondary sexual characteristics or the absence of menarche by age 16 regardless of the presence of normal growth and development of secondary sexual characteristics. In contrast, secondary amenorrhea is defined as the cessation of previous menses for more than 6 months. The etiology of amenorrhea can be seen from its anatomical and functional stratified components. Compartment I is disorders of the uterus and patency (outflow tract), such as Asherman's Syndrome, Tuberculous Endometritis. Compartment II is a disorder of the ovaries such as Turner Syndrome. Compartment III is a disorder of the pituitary such as pituitary adenoma, Empty Sella Syntrome, Sheehan's syndrome. Compartment IV, namely disorders of the hypothalamus or central nervous system such as Hypothalamic Amenorrhea, namely deficiency of GnRH pulsatile secretion causing disruption of gonadotropin secretion, resulting in impaired follicular maturation and ovulation, in turn, hypothalamic amenorrhea will occur. Based on chromosomal analysis, the cause of primary amenorrhea in 45% of cases is due to gonadal dysgenesis, chromosomal abnormalities or muller duct agenesis.